Strain Engineering and Buffer Layer Design in VO₂ Thin Film Structures: From Phase Transition Mechanisms to Smart Window Applications - Lu, Hao; Justus Liebig University Giessen (My University, 2025)
This dissertation presents two main research directions. First, we investigate the tunability of the metal–insulator transition (MIT) in crystalline VO2 thin films via strain engineering. High-quality VO2 epitaxial films of various thicknesses are deposited on TiO2 (110) substrates using pulsed laser deposition. The resulting strain state depends on the film thickness. This correlation is established by detailed characterization of the structural and electrical properties. VO2 films thinner than 20 nm remain fully strained and exhibit tensile strain along the c-axis of the rutile phase, resulting in an increase of the MIT temperature by up to 30◦C compared to relaxed 300 nm thick films. In thicker films, the strain gradient induces a gradual and spatially varying transition of layered regions from the insulating to the metallic phase upon heating. Second, we investigate the use of rutile-phase CuxTi1-xO2 as a buffer layer to enable low-temperature growth of thermochromic VO2. Specifically, we examine the influence of copper incorporation on the structural and optical properties of TiO2. Copper incorporation promotes alloy formation and reduces the anatase-to-rutile transition temperature, allowing rutile-phase CuxTi1-xO2 to form during sputtering at temperatures as low as 200◦C, versus 600◦C for pure rutile TiO2. We fabricate and investigate a tri-layer structure comprising a CuxTi1-xO2 buffer layer, a thermochromic VO2 layer, and an anatase TiO2 antireflection coating. Although increasing Cu content reduces the optical transparency of CuxTi1-xO2 in the visible range, the performance of the tri-layer structure approaches that of an analogous structure using rutile TiO2 as the buffer layer. Thus, employing a rutile CuxTi1-xO2 buffer layer enables the fabrication of VO2-based multilayer structures for thermochromic applications at temperatures compatible with industrial sputtering systems.
Kontrolle der Verspannung und Pufferschichtdesign in VO₂-Dünnschichtsystemen: Von den Mechanismen des Phasenübergangs zu Anwendungen in intelligenten Fenstern
Keywords: ddc:530